The Revolution of Blockchain in Digital Payment Systems: Legal Implications and Regulatory Challenges - Arif, Zainal; ., Zulfitria; Supyadillah, Asep; Irfan, Ahmad; Taufik, Azhar (Journal of Ecohumanism, 2024)
This study aims to analyze the revolution of blockchain technology in digital payment systems, as well as explore the legal implications and regulatory challenges faced in its adoption. The research method used is a qualitative approach with normative analysis, utilizing data sources from literature, applicable regulations, and case studies from various countries. The results of the study show that blockchain has changed the digital payment landscape by providing solutions to improve efficiency, security, and transparency, this technology also poses legal challenges related to privacy, data security, and consumer protection. Differences in regulatory approaches between countries, especially between developed and developing countries, result in legal uncertainty that can hinder further adoption. These findings emphasize the importance of developing a uniform and adaptive regulatory framework to support blockchain innovation while maintaining stability and protection in the financial sector. This study provides important insights for policymakers and practitioners in the financial sector in dealing with complex regulatory challenges related to the adoption of blockchain technology.